Pengaruh Likuiditas, Leverage Dan Ukuran Perusahaan Terhadap Kinerja Keuangan Pada Perusahaan Property Dan Real Estate - Fitriyah, Nayla Rahmi; Syaiful (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The learning is targeted at observing each variable raised as the topic of this learning. This learning will be held at housing manufacturing companies that have been verified on the IDX since 2022-2023. This learning takes a quantitative approach using purposive sampling. To analyze the data through testing classical assumptions, descriptive statistics, as well as hypotheses from the media multiple regression method SPSS 25.0. The total learning sample is worth 100. Based on the learning, It is observed that all independent variables have a significant effect on the dependent variable which has been verified on the BEI since2022-2023. However, partially the liquidity variable affects financial performance, while the leverage variable and company size have no partial effect on financial performance.